Kandungan Protein Kasar dan Serat Kasar Pada Daun Kangkung Air (Ipomoea aquatica) yang Difermentasi [Crude Protein Content and Crude Fiber On Watercress Leaf Water (Ipomoea aquatica) in Fermented Processing] - Agustono, Agustono; Andy Setyo Widodo; Widya Paramita (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
Abstract Watercress leaf water availability (Ipomoea aquatica) in the aquatic environment, can be use as feed supplement, because it has enough protein, but the content is very high crude fiber. Fermentation is a good way to improve the value of water content of watercress leaf water. The purpose of this research to increase the protein content and lower crude fiber content levels. The study was conducted in the Animal Husbandary Departement Faculty of Veterinery Medicine of Airlangga University. This research used watercress leaf water and probiotics as fermenters. Treatments is used 5 with the size of different doses of probiotics, namely P0 (0%), P1 (2%), P2 (4%), P3 (6%), and P4 (8%), of each treatment is repeated 4 times, and the fermentation process carried out for 7 days, then analysed proximat. Experimental design used is Complete Random Design (RAL). Analysis of data using various print and to determine the best treatment performed Duncan's Multiple Range test. The result showed that the use of probiotics in the fermentation process watercress leaf water the real impact of increased crude protein and crude fiber decreased. Crude protein content increased from 23,9945% (P0) to 28,1079 (P4). Crude fiber decreased from 16.1744% (P0) to 11.8341% (P3). The use of probiotics are most effective in the fermentation process watercress leaf water at doses of 8%.